Isolation and characterization of key contributors to the "kokumi" taste in soybean seeds. Issue 11 (2nd November 2017) - Shibata, Masayuki; Hirotsuka, Motohiko; Mizutani, Yukiko; Takahashi, Haruya; Kawada, Teruo; Matsumiya, Kentaro; Hayashi, Yukako; Matsumura, Yasuki
Abstract: The water extract of soybean seeds ( Glycine max (L.) Merr.) is nearly tasteless, but "kokumi" taste sensation was confirmed upon addition of a basic umami solution containing glutamic acid, inosine monophosphate, and sodium chloride. To identify the key contributors to the "kokumi" taste sensation in soybean seeds, sensory-guided fractionation, taste sensory analyses, and LC–MS/MS analyses were utilized. γ-glutamyl-tyrosine and γ-glutamyl-phenylalanine were identified as contributors to "kokumi taste"; specifically, these γ-glutamyl peptides imparted the "kokumi" taste sensation at a low taste threshold in a basic umami solution. Raffinose and stachyose, which are sufficiently present in soybean seeds, exhibited a synergistic effect in regard to the enhanced "kokumi" taste sensation of γ-glutamyl peptides. This is the first report that the combined use of γ-glutamyl peptides and oligosaccharides can increase the "kokumi" intensity, which suggests that soybean extracts or soymilk can be used to enhance the "kokumi" taste sensation in food products. Abstract: : The combined use of γ-glutamyl peptides and oligosaccharides can increase the "kokumi" taste intensity.